Vignettes in Patient Safety - Volume 3 2018
DOI: 10.5772/intechopen.73155
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Culture in Tunisia: Defining Challenges and Opportunities

Abstract: Background: Although adverse events in health care have been a center of attention recently, patient safety culture in primary care is relatively neglected. This study aimed to provide a baseline assessment of patient safety culture in the primary healthcare centers and explore its associated factors. Methods: This is a multicenter cross-sectional descriptive study. It was conducted in the center of Tunisia over a period of 4 months. It surveyed 30 primary healthcare centers, thus 251 staff members. It used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…However, our results were comparable to those reported in the Belgian and French studies where the score for this dimension was less developed with 70% and 72.9% respectively [25,30]. For Tunisian studies, our score was better than that found in the study of Bouafia et al (63.3%) [12] and Ben Rejab et al [13] and similar to that found in the study of Mallouli et al [14], but this does not mean that this dimension is well developed, it still requires a major challenge to overcome.…”
Section: Data Collection and Ethical Considerationsupporting
confidence: 90%
See 4 more Smart Citations
“…However, our results were comparable to those reported in the Belgian and French studies where the score for this dimension was less developed with 70% and 72.9% respectively [25,30]. For Tunisian studies, our score was better than that found in the study of Bouafia et al (63.3%) [12] and Ben Rejab et al [13] and similar to that found in the study of Mallouli et al [14], but this does not mean that this dimension is well developed, it still requires a major challenge to overcome.…”
Section: Data Collection and Ethical Considerationsupporting
confidence: 90%
“…In total with 9 dimensions out of 10 to be improved according to our results and according to other recent studies carried out in our country [13,14], patient safety seems to be an axis of work to be developed in the Tunisian health system in general.…”
Section: Data Collection and Ethical Considerationsupporting
confidence: 76%
See 3 more Smart Citations